Indoor Environmental Conditions and Pulmonary Tuberculosis in Riverbank Settlements: A Cross-Sectional Study in Banjarmasin, Indonesia - Junaidi Junaidi; Zulfikar Ali As; Muhammad Pahruddin; M. Rizki Imanuddin (Gema Lingkungan Kesehatan, 2026)
Pulmonary tuberculosis (TB) remains a major public health problem in Indonesia, particularly in densely populated riverbank settlements where housing conditions may influence airborne infection risk. However, empirical evidence linking household environmental measurements with TB occurrence in such settings remains limited. This study examined the relationship between indoor environmental conditions and pulmonary TB status among households living along the Martapura River in Banjarmasin. A cross-sectional study was conducted involving 60 households, consisting of 30 TB cases and 30 controls. Indoor temperature, humidity, ventilation area, occupant density, and airborne microbial count were measured using standardized environmental and microbiological procedures. Associations between environmental indicators and TB status were analyzed using chi-square tests and odds ratios (OR) with 95% confidence intervals. None of the measured indoor environmental variables showed a statistically significant association with pulmonary TB status (all p > 0.05). Although most households exhibited high humidity, inadequate ventilation, and elevated occupancy, these conditions were similarly distributed between case and control groups, resulting in non-significant effect estimates. The study did not find evidence of a significant association between indoor environmental quality and pulmonary TB status in riverbank settlements. The findings should be interpreted in light of the environmental homogeneity across households and the study’s limited sample size. Further research incorporating larger samples and multivariable approaches is needed to better understand the environmental determinants of TB in similar high-density settings.